Ecological observations on the earwig, Labidura riparia Pallas (Dermaptera:Labiduridae) inhabiting honey bee colonies - Abd-Elgayed, A.A.; Owayss, A.A. (2007)
The present study was carried out for two successive seasons, 2005 and 2006, in an apiary situated at Beni-suif governorate to evaluate the role of the predator earwig, Labidura riparia Pallas, inhabiting honey bee colonies. Also, a laboratory experiment was conducted in the Fac. Agric., Fayoum Univ. to study the predation potential when feeding on both larvae and pupae of greater wax moth, Galleria mellonella L. Obtained results indicated that the presence of this predator was continuously occurred, mellonella, and it has not been observed attacking bees in tested colonies. Insignificant difference was found between the population of target predator and weather factors, so it is suggested that this predator feeds on G. mellonella stages and may be on other insects visiting or inhabiting bee colonies. It was observed that individuals fed, in laboratory, on larvae and pupae of G. mellonella survived during the test period (30 days), while those unfed had died within 2-7 days of starvation. Daily food consumption for female predator seems to be greater than that for male.
Includes reference.
Summary in Arabic.
Summary in Arabic.
1
Keywords: Insects -- Ecology; Earwigs; Honeybee